Trend and Challenges of BIM Training Acceptance in the Construction Industry in Selangor - WONG, NGIIK ZHING; Peniel Ang Soon Ern (Progress in Engineering Application and Technology, 2021)
Building Information Modelling (BIM) is extensively known as one of the innovations of Information Technology (IT), globally used as a platform to promote collaborative and integrated working environments in the construction project management. Previous study shows that challenges to BIM implementation include lack of skilled personnel who is competent and has capability in using BIM effectively and lack of proper training by the local authorities and have a little knowledge of BIM.  The main objectives of this study are to determine the current BIM training trend of contractors in the Malaysia construction industry and to identify challenges of BIM training acceptance in the construction industry in Malaysia. Out of 300 questionnaires distributed to G5 to G7 contractors, only 60 contractors’ firms responded. The data were analysed using statistical package of social science (SPSS) version 26 and Microsoft Excel to obtain frequency, percentage and mean value. This findings from the current trend of BIM training shows that very little company actually implementing BIM. Majority of the company do not have any clear strategies BIM training. However, there are several challenges of BIM training acceptance in construction industry such as high cost of software and updates, high cost of implementing the process and technology and lack of support and incentive from government and professional bodies. This research justifies the need for more strategic provision by the government to ensure greater acceptance of the construction industry towards BIM training.